Positive and negative work performances and their efficiencies in human locomotion - Margaria, R. (Internationale Zeitschrift für angewandte Physiologie einschließlich Arbeitsphysiologie, 1968)
Walking at a constant speed on a steep incline, the ratio of the mechanical work performed, as calculated by the body lift, to the energy expended, as calculated by the oxygen consumption, generally referred to as "efficiency", is independent of the incline, and it amounts to 0.25 walking uphill and to — 1.2 walking downhill. These values can be regarded as the "efficiency" values for positive (uphill) and negative (downhill) work. Walking on the level or on a mild incline, both positive and negative work are performed within the step cycle. When an equal amount of positive and negative work is performed (level walking or running) the energy level of the body at the end of the performance does not change, and the "efficiency" as calculated amounts to 0.207. This work may be consideredwasted: it reaches a maximal amount on the level of 0.044 kgm/m kg walking, and of 0.088 kgm/m kg running. For this reason a constant pull in the direction of the movement cannot replace completely the pull given by the muscles, as when other systems of progression such as cycling, skiing, skating etc. are adopted. By far the greatest amount of energy spent in walking or running at a constant speed is spent in positive work performance to counteract the deceleration (negative work) taking place at the end of each step. Very little energy is supplied for internal work, i.e. to meet the resistance to progression due to friction within the body or at the contact of the foot with the soil.